Patterns of differential gene expression in adult rotation - resistant and wild - type western corn rootworm digestive tracts - Chu, Chia Ching (2015)
Fil: Zavala, Jorge Alberto. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Biología Aplicada y Alimentos. Cátedra de Bioquímica. Buenos Aires, Argentina.